2021
DOI: 10.1155/2021/8892085
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Comparison of Moderate Conscious Sedation and Anesthesia Assistance for the Performance of Endoscopic Retrograde Cholangiopancreatography (ERCP)

Abstract: Objectives. Recent trends have favored the use of anesthesia personnel more frequently for advanced endoscopic procedures. We hypothesize a selective sedation approach based on patient and procedural factors using either moderate conscious sedation (MCS) or general anesthesia (GA) will result in similar outcomes and safety with significant cost savings. Methods. A 12-month prospective study of all adult endoscopic retrograde cholangiopancreatography (ERCPs) performed at a tertiary medical center was enrolled. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Titrated doses of conscious sedation may be adequate in the majority of these procedures. 169 It is important to note that even grade 1 and grade 2 ERCP and diagnostic EUS can at times be challenging and prolonged. Apart from the expected procedural complexity, the patient's anxiety level, BMI, ASA class, cardiopulmonary comorbidity, medication history and tolerance of previous procedures under sedation need to be considered when deciding whether mild/ moderate sedation is adequate in these patients.…”
Section: Level Of Agreement: 100%mentioning
confidence: 99%
“…Titrated doses of conscious sedation may be adequate in the majority of these procedures. 169 It is important to note that even grade 1 and grade 2 ERCP and diagnostic EUS can at times be challenging and prolonged. Apart from the expected procedural complexity, the patient's anxiety level, BMI, ASA class, cardiopulmonary comorbidity, medication history and tolerance of previous procedures under sedation need to be considered when deciding whether mild/ moderate sedation is adequate in these patients.…”
Section: Level Of Agreement: 100%mentioning
confidence: 99%
“…These procedures usually take longer than conventional ones, requiring deeper sedation and more advanced care to enhance sedation practices and intervention against potential complications. Various studies have been published in this context to evaluate the safety and efficacy of sedation practices and dosages, and to compare the effectiveness of combined versus single-drug administration [113][114][115]. For instance, a previous study showed that the efficacy of ESD for early gastric cancer was comparable between intermittent midazolam injection and continuous propofol infusion [116].…”
Section: Othersmentioning
confidence: 99%